(untitled) (Research, Society and Development, 2020)
Brazil has enormous genetic diversity of wild fruit trees in the world. However, little is known about most of these species. In the Southwest of Paraná this diversity can be found, however, due to the anthropic action in recent years it has been observed the fragmentation of the ecosystem, causing genetic erosion, losing genotypes with potential use as native fruit trees. Thus, conservation of genetic resources is essential as strategies to reduce the damage to the environment and lack of technical information to enhance their use. The objective of this work was to collect information on the location of these fruit trees in eight hundred rural properties. The present work was carried out in rural properties of Dois Vizinhos, Itapejara do Oeste, Verê and São Jorge d’Oeste (PR). The largest number of family farmers who owned on their properties the native fruit trees Surina cherry, jabuticaba tree, uvaia tree, cereja da mata tree, guabiroba tree, guabiju tree, seven capote tree, yellow and red araça tree. A semi-structured questionnaire was applied, which dealt with questions about the presence, management and use of Myrtaceae fruit tree in their properties and the informed consent term. The native fruit trees present in each property were surveyed, as well as farmers age, land area, community distribution, altitude, and other native species found. in order to determine the preference of the species in relation to these attributes. The native fruit trees of the family Myrtaceae are still present in the rural properties of the Southwest of Paraná, but some species are found with a small quantity, making it necessary to preserve them or to use their fruits to obtain the on farm conservation network, maintaining them for sustainable use. The existing jabuticaba tree were all planted, not observing native occurrence.